Some Aspects of a Manufacturing Process Simulation - Chovanec, Alexej; Breznická, Alena (Manufacturing Technology Journal, 2017)
The submitted paper presents possibilities of a simulation for a real manufacturing process in a company taking the risks into consideration. The risks may result from various sources in manufacturing environment. The most significant ones include a human factor, the processes in general and environs where the manufacturing process takes place. Risk can be viewed as a state where there is a possibility of a loss but also a hope of gain since one would never jeopardize the loss if there were no chance of a win. Because of the argument that a risk is perceived differently depending on the observer's experiences and objectives, it has become increasingly important in organisations to create awareness and gain information of potential risks. The paper is aiming to present the possibilities how to avoid such risks or to decrease them to an acceptable level through simulation and modelling tools.
Keywords: Risk; Manufacturing industry; Experiments; Simulations